Code Generation For Csm/Ecsm Models In Cosma Environment - Waldemar Grabski; Michał Nowacki (Computer Science, 2007)
The COSMA software environment, developed in the Institute of Computer Science, WUT,was designed primarily for model checking of reactive systems specified in terms of ConcurrentState Machines (CSM). However, COSMA supports also Extended CSM (ECSM).The extensions allow for using complex data types and pieces of C/C++ code, attributedto CSM states and/or transitions. Because of these extensions, ECSM models cannot beverified by model checking, but they can be used as an intermediate step in code generation.The underlying CSM represent then the flow of control within cooperating components andthe communication among them while the extensions specify the data structures and thedetails of their processing.The paper discusses the code generation from ECSM diagrams. The approach is illustratedwith an example.